Pengaruh Experiential Marketing Dan Kepercayaan Merek (Brand Trust) Terhadap Kepuasan Pelanggan Melalui Keputusan Pembelian (Studi Kasus pada Konsumen Larissa Aesthetic Center cabang Panjaitan, Semarang) - Lintang Imania; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2018)
The importance of paying attention to skin care has been done by Indonesian people since a few years ago, but there are still some people who think that such skin care is a waste of time and increase family expenditure. Over time people are more open to care for their skin. Based on these things, then emerged skin clinics that offer various types of facial, hair and body care. One such skin clinic is the Larissa Aesthetic Center that offers a wide range of skin care and skin care products using natural ingredients that consumers, both women and male consumers, need. The purpose of this research is to know the influence between experiential marketing, brand trust, and purchasing decisions towards customer satisfaction. Based on the result of calculation analysis of WarpPLS can be explained that the result of direct impact test on this research model show result of positive and significant influence. The results of indirect effect test on the model showed a positive influence, but there is no significant experiential marketing variables, as well as the positive and significant influence on brand trust variables. Author can give some advise that are, do routine evaluation every month and keep the equipment for hygiene treatment and therapist’s hand to see whether with satisfied or disatisfied of consumers in experiencing use the treatment or product of Larissa Aesthetic Center branch Panjaitan, Semarang.